2014
DOI: 10.1037/a0034747
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a mobile intervention for heavy drinking and smoking among college students.

Abstract: Nearly all college student smokers also drink alcohol, and smoking and heavy-episodic drinking (HED) commonly co-occur. However, few studies have examined the factors that concurrently influence smoking and HED among college students and, to date, no interventions have been developed that target both HED and smoking in this population. The objective of the current study was to develop and evaluate a mobile feedback intervention that targeted HED and smoking. Participants (n = 94) were non-treatment seeking col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
181
0
20

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(204 citation statements)
references
References 56 publications
3
181
0
20
Order By: Relevance
“…To do so, we compared the clinical outcomes of the JITAI with "treatment-as-usual" (face-to-face treatment). Consistent with previous JITAI studies [18,[32][33][34][35], we found that the implementation of personalized and time-varying JITAI approach improved the outcome of traditional evidence-based treatment. In the current study, we found that the iREST intervention was associated with slightly higher rates-although not statistically significant-of response and remission compared to our previous traditional behavioral approach [16].…”
Section: Principal Resultssupporting
confidence: 80%
“…To do so, we compared the clinical outcomes of the JITAI with "treatment-as-usual" (face-to-face treatment). Consistent with previous JITAI studies [18,[32][33][34][35], we found that the implementation of personalized and time-varying JITAI approach improved the outcome of traditional evidence-based treatment. In the current study, we found that the iREST intervention was associated with slightly higher rates-although not statistically significant-of response and remission compared to our previous traditional behavioral approach [16].…”
Section: Principal Resultssupporting
confidence: 80%
“…The review studies also suggest the possible benefit of application as they can provide audio, video and text-based intervention under a single platform. They are possibly cost effective, easy to deliver and implement [39][40][41] . All studies have reported the positive influence of mobile applications on quit rate.…”
Section: Discussionmentioning
confidence: 99%
“…A trial testing the effectiveness of a 14-day mobile feedback intervention jointly targeting smoking and HED resulted in a decrease in the number of cigarettes smoked compared to a minimal assessment control condition, but did not reduce HED or concurrent smoking and drinking at 1 month follow-up [5]. Given the ongoing, significant public health impact of alcohol and tobacco use, more research is needed to determine how best to harness digital tools to target smoking and HED in young adults.…”
Section: Introductionmentioning
confidence: 99%